Ramet demography of Aechmea distichantha (Bromeliaceae) in two contrasting years in the understory and open areas of a South American xerophytic forest - Barberis, Ignacio Martín (2020)
Fil: Fil: Barberis, Ignacio Martín. Universidad Nacional de Rosario. Facultad de Ciencias Agrarias; Argentina